FUNCTIONAL CONSTIPATION IN CHILDREN : A SYSTEMATIC REVIEW - Malanda, Yoga (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2023)
It is essential to test and diagnose children as soon as possible for functional constipation (FC), which is considered a substantial burden of illness in children. When treated in a timely manner and with the proper medication, babies who have FC have a better chance of making a full recovery. It is estimated that inflammatory bowel disease is responsible for up to 25% of pediatric gastroenterologist visits and 3% of all pediatric outpatient visits globally. It is difficult to estimate the real prevalence of FC in children as a result of the variability of the studies in terms of target population sample, diagnostic criteria, participant ethnicity and environment, technique of data gathering, and lifestyle and psychological characteristics, amongst other considerations. It is possible that the key causes for the worldwide variation in prevalence among studies that have been published are the absence of consensus on diagnostic criteria and cultural variations. Probiotics have the capacity to improve the balance between species, impact intestinal motility by creating lactic acid and short-chain amino acids, and stimulate gut peristalsis by adjusting stool pH. Additionally, probiotics have the potential to increase the number of short-chain amino acids produced in the body. A wide variety of probiotic strains have been the subject of a significant number of investigations. On the other hand, there are not enough evidence available at this time to support the use of probiotics in children who suffer from chronic constipation.